Discectomy for malocclusion with anterior open bite due to posterior disc displacement without reduction. Issue 2 (March 2018) - Umebayashi, Mayumi; Ohba, Seigo; Miura, Kei-ichiro; Koga, Takamitsu; Shidou, Rena; Kawasaki, Takako; Asahina, Izumi
Abstract: Posterior disc displacement (PDD) is a rare temporomandibular joint disorder. PDD without reduction sometimes causes malocclusion. Splint therapy, arthrocentesis and manipulation are sometimes undertaken to reposition the disc in PDD without reduction. However, these treatment strategies are not always effective for chronic PDD without reduction. Here, we report a case of a 36-year-old Japanese male who presented with malocclusion with an anterior open bite. He was diagnosed with chronic PDD without reduction, and underwent a discectomy. His occlusion improved after surgery and became stable. This case suggests that a discectomy is an effective treatment option for malocclusion with anterior open bite caused by chronic PDD without reduction.